Current status of treatment for malignant ovarian sex cord-stromal tumors - Fang Chunli; Chen Hailin; Zhou Yingying; Xiao Huajing; Xu Boqun (Discover Oncology)
Abstract Malignant ovarian sex cord-stromal tumors belong to a specific type of ovarian epithelial carcinoma, and their prognosis is related to the kind of pathology. Unlike epithelial ovarian cancer, most malignant ovarian sex cord-stromal tumors are low-grade malignant and have a good prognosis. Still, they have a tendency to recur in the long term, and the mortality rate of patients after recurrence is high. Surgery is the preferred treatment for malignant ovarian sex cord-stromal tumors with chemotherapy, and other comprehensive treatments. Recurrent and metastatic malignant ovarian sex cord-stromal tumors usually require systemic adjuvant chemotherapy, and hormonal or targeted therapy may be attempted on an individualized basis in cases where chemotherapy fails.